English Language Training in the Ukrainian Military Academies: Problems for Teachers and Curriculum Developers - LAGODYNSKYI, Oleksandr (Journal of Education, Technology and Computer Science, 2013)
The article identifies major problems the teachers and curriculum developershave with the English Language Training in the Ukrainian military academies. Itgives recommendations on how to solve them in order to improve language interoperabilityof the Ukrainian armed forces with the foreign military.